Role of chaihu yujin decoction in cholecystitis: a systematic investigation integrating multi-omics and experimental validation - Feng Xu; Jia-Han Xu; Xiao-Min Chen; Kai-Li Mao; Jie Hu; Hong-Liang Zheng; Huan-Huan Xia; Zhi-Hui Zhang; Qiu-Ting Lin (Functional & Integrative Genomics, 2026)

Retraction Note: Exploring the potential of miR-9a-5p in circadian rhythm and cognitive recovery following brain injury in neonatal rats - Changqin Han; Lin Li; Yajing Yun; Chenxi Feng; Meifang Jin; Xin Ding; Bin Sun; Lixiao Xu (Functional & Integrative Genomics, 2026)

RETRACTED ARTICLE: Exploring the potential of miR-9a-5p in circadian rhythm and cognitive recovery following brain injury in neonatal rats - Changqin Han; Lin Li; Yajing Yun; Chenxi Feng; Meifang Jin; Xin Ding; Bin Sun; Lixiao Xu (Functional & Integrative Genomics, 2025)

Girdin acts as an oncogene in gastric cancer by regulating AKT/GSK3β/β-catenin signaling - Yun Wang; Qiang Fu; Yun-jian Tao; Sheng-nan Ying; Heng-gao Zhong; Yue Zhu; Xiao-han Qian; Lin Miao; Li-hua Yang (Functional & Integrative Genomics, 2023)
ThE present work focused on exploring Girdin expression within gastric cancer (GC), examining the effect of Girdin on the cell phenotype of GC, and clarifying the underlying mechanisms. Girdin expression in GC samples was identified by immunohistochemistry (IHC) and quantitative real-time PCR (qRT-PCR) assays. Girdin-targeting siRNAs were transfected into GC cells; later, we examined GC cell proliferation, migration, invasion, and apoptosis, respectively. Additionally, the protein expression was examined through Western blotting assay. Moreover, the tumor implantation experiment was conducted for examining Girdin knockdown in vivo. The results showed that Girdin expression elevated within GC samples, which was associated with the dismal prognostic outcome. Girdin knockdown suppressed GC cell proliferation, migration, and invasion, and enhanced apoptosis and cell cycle arrest. Girdin promoted the phosphorylation of AKT, GSK3β, and β-catenin. Moreover, Girdin inhibited the phosphorylation of β-catenin. Girdin suppressed cell apoptosis and stimulated cell migration and invasion, while AKT inhibitor (MK2206) treatment reversed the effect of Girdin overexpression, and GSK3β inhibitor (CHIR99021) treatment enhanced the effect of Girdin overexpression on GC cells. Besides, Girdin delayed tumor growth in vivo. In conclusion, Girdin was abnormally expressed in GC samples, which promoted the development of GC by regulating AKT/GSK3β/β-catenin signaling.

Development of mitochondrial simple sequence repeat markers to simultaneously distinguish cytoplasmic male sterile sources in cotton - Yongqi Li; Meng Zhang; Kashif Shahzad; Yang Han; Xuexian Zhang; Liping Guo; Tingxiang Qi; Huini Tang; Hailin Wang; Xiuqin Qiao; Juanjuan Feng; Zhongxu Lin; et al. (Functional & Integrative Genomics, 2023)

Identification and bioinformatics analysis of differentially expressed milk exosomal microRNAs in milk exosomes of heat-stressed Holstein cows - Yue Wang; Jian Fang; Han-Fang Zeng; Ji-Feng Zhong; Hui-Xia Li; Kun-Lin Chen (Functional & Integrative Genomics, 2022)

Expansion and evolutionary patterns of GDSL-type esterases/lipases in Rosaceae genomes - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Jiangliu Yu; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Systematic analysis and comparison of the PHD-Finger gene family in Chinese pear (Pyrus bretschneideri) and its role in fruit development - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)